Measure of Noncompactness and Nondensely Defined Semilinear Functional Differential Equations with Fractional Order - MOUFFAK BENCHOHRA (Cubo, 2010)
This paper is devoted to study the existence of integral solutions for a nondensely defined semilinear functional differential equations involving the Riemann-Liouville derivative in a Banach space. The arguments are based upon Mönch’s fixed point theorem and the technique of measures of noncompactness. Este artículo es dedicado al estudio de existencia de soluciones integrales para ecuaciones diferenciales funcionales semilineales envolviendo la derivada de Riemann-Liouville en un espacio de Banach. Los argumentos se basan en un teorema de punto fijo de Mönch y la técnica de no compacidad.